The development, validity, and reliability study of addiction profile index (bapi)’s short form - Ögel, Kültegin; Güneş, Remzi; Koç, Ceren; Görücü, Serap; Başabak, Aslı (Journal of Dependence, 2015)
Objective: The objective of this study is to develop and conduct the reliability and validity tests of the short form of Addiction Profile Index (BAPI), which is a culturally-sound risk screening scale that determines alcohol and substance usage level.Method: The sample of this study consisted of 1087 individuals chosen from a penitentiary. All the participants were administered to BAPI, CAGE Scale and AUDIT Scale. In order to develop the short form of BAPI, descriptive factor analysis, reliability analysis and validity analysis were applied.Results: The analysis yielded 11-item short version of BAPI that evaluates alcohol and substance usage together. Internal validity analysis has revealed that Cronbach-α coefficient for BAPI-Short form was 0.89. Correlation coefficients of BAPI-Short form were found to be 0.96 with BAPİ, 0.78 with CAGE and 0.81 with AUDIT.Conclusion: Considering its psychometric properties of the scale, BAPI-Short form is evaluated as a valid and reliable questionnaire and can be used as a severity scale including different components of dependency.
Keywords: Addiction severity; scale development; Addiction Profile Index (BAPI)